2010
DOI: 10.1017/s1751731110000443
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behaviour of sheep fed lucerne v. grass hays with controlled post-ingestive consequences

Abstract: Understanding what determines feeding behaviour in herbivores is essential to optimise the use of forages in breeding systems. Herbivores can evaluate foods by associative learning of their pre-ingestive characteristics (taste, odour, etc.) and their postingestive consequences. Post-ingestive consequences are acknowledged as influencing intake and food choices, but the role of pre-ingestive characteristics is still being debated. Our experiment was designed to test their separate effects on daily dry matter i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 32 publications
(43 reference statements)
1
19
0
7
Order By: Relevance
“…Does the palatability of food sensory characteristics affect intake and feeding pattern? Using two good-quality forages (lucerne and grass hays) with different sensory characteristics, daily dry matter intake did not differ when controlling for post-ingestive consequences (Favreau et al, 2010c; Figure 1). Greenhalgh and Reid (1971) found similar results when offering two good-quality forages (dried grass and meadow hay), whereas they demonstrated that sensory characteristics influenced the daily intake of a lowquality forage (oat straw) compared with a good-quality forage (dried grass; Figure 1).…”
Section: Sensory Characteristics: a Way To Get Pleasurementioning
confidence: 99%
See 4 more Smart Citations
“…Does the palatability of food sensory characteristics affect intake and feeding pattern? Using two good-quality forages (lucerne and grass hays) with different sensory characteristics, daily dry matter intake did not differ when controlling for post-ingestive consequences (Favreau et al, 2010c; Figure 1). Greenhalgh and Reid (1971) found similar results when offering two good-quality forages (dried grass and meadow hay), whereas they demonstrated that sensory characteristics influenced the daily intake of a lowquality forage (oat straw) compared with a good-quality forage (dried grass; Figure 1).…”
Section: Sensory Characteristics: a Way To Get Pleasurementioning
confidence: 99%
“…This can be achieved by (i) measuring short-term preferences and/or intake since it can be assumed that the postingestive consequences of the food have not been felt by the animal yet (Favreau et al, 2010c), (ii) by using an ingredient able to modify the sensory properties of the food without adding any post-ingestive consequence (e.g. a calorie-free sweetener such as saccharin; Hellekant et al, 1994), (iii) by offering the different food items simultaneously since it increases the difficulty for the animal to identify which food item is responsible for which consequence (Duncan and Young, 2002;Favreau et al, 2010b), and/or (iv) by checking, with a conditioning procedure, that the intake of the added sensory modifier does not cause any post-ingestive consequence at the dose rate involved in the study (Gherardi and Black, 1991;Favreau et al, 2010a).…”
Section: Sensory Characteristics: a Way To Get Pleasurementioning
confidence: 99%
See 3 more Smart Citations